2002
DOI: 10.1042/cs1020187
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor and its receptor, Flt-1, in the plasma of patients with coronary or peripheral atherosclerosis, or Type II diabetes

Abstract: Since atherosclerosis is characterized by endothelial damage, re-growth seems likely to be occurring in order to repair or replace injured cells. Angiogenic vascular endothelial growth factor (VEGF), a likely mediator of these events, acts on the endothelium via a specific receptor, Flt-1. We hypothesized that patients with different manifestations of atherosclerosis, and others with diabetes, would have altered plasma levels of VEGF and Flt-1 compared with healthy individuals. Accordingly, 70 patients with pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
119
3
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(133 citation statements)
references
References 30 publications
9
119
3
2
Order By: Relevance
“…As the inter-endothelial junction discontinuities are less than 3 nm and can only account for the passage of small molecules (Michel and Curry 1999), it was generally considered that macromolecules pass through the endothelium in transcellular way, most likely to be mediated by caveolae. Elevated plasma VEGF was observed in both diabetic patients with atherosclerosis and diabetic model of rabbit (Blann et al 2002;Laakso 2008). In vitro studies demonstrated that high glucose induced VEGF in mesangial cells, glomerular podocytes, and retinal pigmented epithelial cells (Senger et al 1990;Hoshi et al 2002;Sone et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…As the inter-endothelial junction discontinuities are less than 3 nm and can only account for the passage of small molecules (Michel and Curry 1999), it was generally considered that macromolecules pass through the endothelium in transcellular way, most likely to be mediated by caveolae. Elevated plasma VEGF was observed in both diabetic patients with atherosclerosis and diabetic model of rabbit (Blann et al 2002;Laakso 2008). In vitro studies demonstrated that high glucose induced VEGF in mesangial cells, glomerular podocytes, and retinal pigmented epithelial cells (Senger et al 1990;Hoshi et al 2002;Sone et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, high concentrations of PAI-1 and subsequent downregulation of fibrinolysis have been implicated in the increasing morbidity, mortality and risks for thrombotic disease in diabetic patients [18,19]. VEGF and sFLT-1 may also play a role in the pathophysiology of atherosclerosis by initiating and propagating angiogenesis, and thereby providing a passage for inflammatory cells to the site of injury [29]. Increased concentrations of VEGF and sFLT-1 have been reported in patients with diabetes, and they may play a role in the development of diabetic nephropathy and retinopathy [20].…”
Section: Discussionmentioning
confidence: 99%
“…Date are expressed as mean±standard deviation (SD). The difference is considered to be significant at P-value of <0.05 (in bold) Blann et al (2002) assessed the expression of angiogenic factors in plasma of patients with type 2 diabetes, and revealed significantly higher VEGF concentrations in diabetic patients comparable with healthy subjects. Similarly higher VEGF concentrations in plasma of patients with PAD irrespective of diabetes (non-)coexistence were reported by Botti et al (2012).…”
Section: Discussionmentioning
confidence: 99%